2014
DOI: 10.1073/pnas.1324135111
|View full text |Cite
|
Sign up to set email alerts
|

Remote loading of preencapsulated drugs into stealth liposomes

Abstract: Loading drugs into carriers such as liposomes can increase the therapeutic ratio by reducing drug concentrations in normal tissues and raising their concentrations in tumors. Although this strategy has proven advantageous in certain circumstances, many drugs are highly hydrophobic and nonionizable and cannot be loaded into liposomes through conventional means. We hypothesized that such drugs could be actively loaded into liposomes by encapsulating them into specially designed cyclodextrins. To test this hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(89 citation statements)
references
References 70 publications
4
85
0
Order By: Relevance
“…However, the contribution of this factor on liposomal instability is expected to be minimal or insignificant [43] proven by our in-vitro and cell toxicity tests. While our current method resulted in RES-CD being passively encapsulated within the aqueous core, it has been previously reported that functionalized CD molecules may also be remotely loaded into liposomes [44]. The strategy, which utilizes pH or ion gradients to drive molecular entrapment, can substantially enhance the total effective load of CD-drug complex into the formulation.…”
Section: Stability Studymentioning
confidence: 94%
“…However, the contribution of this factor on liposomal instability is expected to be minimal or insignificant [43] proven by our in-vitro and cell toxicity tests. While our current method resulted in RES-CD being passively encapsulated within the aqueous core, it has been previously reported that functionalized CD molecules may also be remotely loaded into liposomes [44]. The strategy, which utilizes pH or ion gradients to drive molecular entrapment, can substantially enhance the total effective load of CD-drug complex into the formulation.…”
Section: Stability Studymentioning
confidence: 94%
“…The heat increased the fluidity and thus permeability of the liposomes toward the cyclodextrin (remote loading technique). 334 The other method employed a dehydration− rehydration technique. 335 Liposome−quantum dots hybrids, 336 hybrid capsules of alginate plus guar gum encapsulated with liposomes, 337 and hydrogel-in liposomes 338 to encapsulate several drugs have been described in separate studies.…”
Section: Liposomal Delivery: Hybrid Liposomesmentioning
confidence: 99%
“…Thus, drug-delivery systems have become one of the most promising applications for health care 4, 5, 6. A large number of strategies have been studied, but for application, drug-delivery systems must overcome issues surrounding bioavailability,7, 8 the uncontrollable release of drugs (usually due to carrier instability),9, 10, 11 loading capacities,11, 12, 13 particle size,14, 15, 16 nanoparticle cellular internalization routes,14, 17, 18 and toxicity 19, 20. The exceptional storage capacities of metal-organic frameworks (MOFs), together with their robustness and structural tailorability, have made them attractive for a wide variety of applications,21, 22 including several promising breakthroughs in biomedicine 9, 10, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33.…”
Section: Introductionmentioning
confidence: 99%